Representation of Diversity in The Little Mermaid (2023) - Myisha, Nabila; Sabila, Dinda; Aini, Dinera Qurrotul; Febrianti, Mayang Anggun; Putri, Farah Malaika (Cultural Narratives, 2024)
As a cultural product of one of the world’s most influential media corporations, the film represents a significant departure from the Eurocentric depictions traditionally associated with Disney princesses. This research aims to identify inclusion and diversity in representing multiculturalism in the movie adaptation of Hans Christian Andersen’s work “The Little Mermaid”. This study employs descriptive qualitative research to explore and analyze the representation of diversity and multiculturalism in the film adaptation of “The Little Mermaid 2023.” Descriptive qualitative research is chosen for its ability to provide detailed descriptions and interpretations of cultural representations while using semiotic theory and film adaptation theory. The result shows that there are differences through the narrative element in both works, especially plot, settings, theme, character, and writing style. Through a semiotic lens, this inclusion of diversity can be seen from the casting of the characters namely, Ariel, Ariel’s sisters, and The Queen. By utilizing the original text and adapting it to a live-action movie, Marshall has contributed to the discussion of multiculturalism to represent the lack of inclusion in diversity and representation derived from the original text through his decision to cast actors and actresses of diverse races while still maintaining the elements of the original text. Its representation of diversity has the potential to challenge entrenched stereotypes and inspire a new generation of media consumers to demand more inclusive storytelling. This research underscores the importance of critically examining how iconic narratives are adapted to address issues of representation.